Material and Socio-Cognitive Effects of Immersive Virtual Reality in a French Secondary School: Conditions for Innovation - Martine Gadille; Caroline Corvasce; Maria Impedovo (MDPI AG, 2023)
The dissemination of innovative pedagogies in French secondary education, under the effect of both educational policies and the spontaneous action of teachers, raises the question of the socio-cognitive and material conditions of the design, appropriation, and use of a 3D VW learning space in school. To answer this question, we study the design of a learning space using a 3D VW and the interactions that emerge between the different actors involved in techno-pedagogical innovation. The case study included 22 5th grade students. The videos recorded concern the use of a scenario-based 3D VW for Mathematics, French and Second Language. The analysis of these scenarios based on co-presence, remote-learning and autonomy retrace the material and socio-cognitive conditions of a changing learning space that co-evolves with identities and the teachers' intent to create meaning within a hybridised institutional and organisational framework.